Pengaruh Nilai-Nilai Sosial, Ekspektasi, Gender, dan Personalitas Terhadap Pilihan Berkarir di Bidang Perpajakan (Studi Empiris Pada Mahasiswa Akuntansi Keuangan Publik Politeknik Negeri Bengkalis) - Enjelina S, Try (Politeknik Negeri Bengkalis, 2024)
The purpose of this study is to determine the influence of social values, expectations, gender and personality on career choices in taxation. The formulation of this research problem is to see whether variable X has an effect on variable Y. This research was conducted at the Bengkalis State Polytechnic campus. The population in this study is students of the Public Financial Accounting Study Program batch 2019-2022. Sampling in this study used the saturated sample method and obtained a sample of 307 respondents. The data analysis technique used is multiple linear regression analysis. The research instrument uses questionnaires that are distributed using google forms and online. The results showed that social values, expectations and personality influenced career choices in taxation by students of the Public Financial Accounting Study Program of Bengkalis State Polytechnic, while gender did not affect career choices in taxation by students of the Public Financial Accounting Study Program of Bengkalis State Polytechnic.Keywords: Social Values, Expectations, Gender, Personality, Career Options in Taxation